Tolerance of ambiguity and language learning strategy of IPGM teacher trainees / Wan Muhaimin Wan Ahmad - Wan Ahmad, Wan Muhaimin (2013)
This study explores the types and usage level of language learning strategies and the degree of tolerance of ambiguity of the Bachelor of Education in Teaching English as a Second Language in a Malaysian Teacher Training Institute (EPGM) in Terengganu. It involved 162 participants who were randomly chosen based on certain criteria set. The study also sought to find out any relationship between language learning strategies and tolerance of ambiguity. For the study, the Strategy Inventory for Language Learning (SILL for EFL/ESL) developed by Oxford (1990) and the Second Language Tolerance of Ambiguity Scale by Elly (1995) were used. It was found that the participants were of high users of different language learning strategies. It shows that language learning strategies are frequently used by them. Students' most preferred language learning strategies were the Metacognitive strategies, while the least preferred strategies were the Affective strategies. Their overall tolerance towards ambiguity was found to be above moderate nearing to high intolerance. This signifies that descriptively they do not exhibit high tolerance that would lead them to accept new and ambiguous language elements unquestioningly, nor do they possess total intolerance that could impede their second language learning process. Correlations between tolerance of ambiguity and the language learning strategies were found to be statistically significant and positively correlated, although modest. It indicates that there is indeed a relationship between those variables.